PLAY BEHAVIOUR OF SELECTED PRIMARY SCHOOL CHILDREN OF ASSAM - KARISHMA BEGUM*; M. PRIYA (The Journal of Research ANGRAU, 2023)
The study aimed to find out the type of play behaviour adopted by the children of primary school in Biswanath, Assam in the year 2022. The size of the sample was 600 primary school children in the age group of 6-8 years selected through random sampling technique. A self constructed questionnaire was used to identify social and non-social play behaviour among the children. The study revealed that children of 8 years had higher social play behaviour when compared to children between ages of 6 and 7 Years. Study also reported that children living in joint family had higher social play behaviour than those of nuclear family. No gender difference in children’s play behaviour was found.